Mediating role of regret feelings in the relationship between consumer expectations, emotions and willingness to buy - Mohammed Abdallrahman; Nidal A. Darwish (Rajagiri Management Journal)
Purpose – The paper aims to investigate the impact of customers’ expectations, negative emotions and regret on consumers' intention to buy Chinese clothing products in the Palestinian market. Design/methodology/approach – This paper used a convenience sampling technique. The path relationship of the study model was analyzed by structural equation modeling (SEM) based on partial least squares (PLS-SEM). Findings – Results showed that regret was affected by the negative feelings that consumers could incur after buying the product. Additionally, negative feelings and regret negatively affected consumers' intention to buy Chinese clothing products, while their expectations positively affected their decisions. However, the mediation effect of regret was approved in the relationship between negative feelings and the intention to buy. Originality/value – This is to certify, that the research paper submitted by us is an outcome of our independent and original work. We have duly acknowledged all the sources from which the ideas and extracts have been taken. The project is free from any plagiarism and has not been submitted elsewhere for publication.